Inovasi Teknologi Beton Self Compacting Concrete Terhadap Panjang Pengaliran (L-Flow) Dengan Variasi Umur Perawatan Beton - Adnan Adnan (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2023)
The aim of this research is to analyze the effect of adding hyperplasticizer and retarder on the compressive strength of self-compacting concrete. Fine aggregate and coarse aggregate from the Jenneberang River, Kab. Gowa. The concrete mix design uses a trial and error mix design for self-compacting concrete by making visual observations, so that the physical conditions of the mixture appear to be sufficient to produce a good mix. The stages of this research, by finding a comparison of the slump flow values ​​of the self-compacting Concrete concrete, then making test objects, after that curing the test objects using the water curing method for 28 days, then testing the compressive strength of the self-compacting Concrete concrete to produce comparison to the compressive strength of normal(conventional) concrete. The results of this research show that self-compacting concrete has a compressive strength value of 46.25 Mpa compared to normal concrete of 45.02 Mpa, an increase of 2.73% compared to normal concrete. And the slump value of normal concrete is 8 - 13 cm, while the slump flow of self-compacting concrete is 63 - 84.9 cm, with a time range between 2.53 - 3.46 seconds, able to reach a diameter of 500 mm on the segregation board.